Perfect phrases for motivating and rewarding employees : hundreds of ready-to-use phrases for encouraging and recognizing employee excellence - Diomond, Harriet; Diamond, Linda Eve (McGraw-Hill, 2010)
The book that helps managers, raise performance, recognize top employees, and clearly communicate, "A job well done!"